An essential review of internet banking services in developing countries - Yadgar M. Hama Khan (e-Finanse: Financial Internet Quarterly, 2019)
In the absence of a literature review for an adoption of internet banking in developing countries, this study was conducted to review and summarize the most evaluated articles in the literature. The significance of this work came from three concepts which are to highlight the concepts of research in developing countries, to accentuate the dominant models which have been used effectively in analyzing the constructs in adopting internet banking, and thirdly, to shed some light on the gaps in the potential applications for the system in the future. The Technology Acceptance Model, Theory of Reasoned Action, Theory of Planned Behaviour, Unified Theory of Acceptance and Use of Technology and Self Designed models have been used by most of the researchers in this review with a higher frequency of the Technology Acceptance Model among them. The results from this review are limited to 28 articles which were selected from a total of 110. The sources were from the search engines of Science Direct, Emerald Insight, Growing Science, International Business Information Management Association and Canadian Central of Science and Education and other different types of journal publications. The factors revealed to have important effects on the acceptance and adoption of the system were trust, perceived ease of use, and perceived usefulness, security and privacy and social influences.
Keywords: M3; 330; TAM; UTAUT; Internet Banking customers; Acceptance; Adoption; Trust